SAT0005 Sle Patients in Emergency. the Evaluation of SLE Patients in Helsinki University Central Hospital Emergency during 2003-2012. (10th June 2014) - Tolonen, J.; Häme, A.; Forss, N.; Harjola, V.-P.; Luosujärvi, R.; Mattila, J.
Abstract : Background: Systemic lupus erytematosus (SLE) is more common in women (∼90% of SLE-patients) and in ∼50% of the patients was the diagnosis set ≤30 y age. The neurological symptoms are not seenvery frequently, but these may be difficult to relate in SLE, especially in emergency (ED). Objectives: The aim of this study was to analyze the proportion of neurological SLE patients in a tertiary University Hospital ED 2003-2012. Methods: We used Helsinki University Central Hospital Meilahti ED electrical database retrospectively. We search all the patients with the SLE diagnosis. The ED visit was interpreted as neurological if the charge for the treatment was allocated for neurologist. We analyzed also the need for the spinal fluid examination in ED. Data was compared statistically by Students' T test for continous parameters and by Mann-Whitney U Test for noncontinous ones. The point for statistical significance was set at p<0.05. Results: 44 SLE patients (male7) made 254 visits in ED 2003-2012. 33% of visits (n=84) were related to SLE. 19% of visits (n=48) were classified as neurological, and 67% of these (n=32) were SLE-related. Spinal fluid examination in ED was needed in 6 visits; 1 bacterial meningitis, 1 septicaemia, 1 tetraparesis, 1 disorientation, 1 hemiparesis and 1 SLE-associated muscle disease. Female SLE patients (mean 6.2) visited almost twice as many times in ER than male ones (mean 3.7). Moreover thirteen female visited ≥7 times in ED as compared to one male. The difference between genders was not, however, significant, p=0.570 and p=0.850, respectively. Indeed SLE-patients with neurological symptoms visited in ED significantly more often than those without (p=0.007). Conclusions: SLE was not extremely common diagnosis in our ED. Female SLE patients were overrepresented. In 2/3 patients with neurological symptoms seemed these to be SLE-related. SLE-patients with neurological symptoms visited more often in ED than those without. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2234